The Case for Animal Privacy in the Design of Technologically Supported Environments - Paci, Patrizia; Mancini, Clara; Nuseibeh, Bashar (Frontiers in Veterinary Science, 2022)
Privacy is an essential consideration when designing interactive systems for humans. However, at a time when interactive technologies are increasingly targeted at nonhuman animals and deployed within multispecies contexts, the question arises as to whether we should extend privacy considerations to other animals. To address this question, we revisited early scholarly work on privacy, which examines privacy dynamics in non-human animals (henceforth ‘animals’). Then, we analysed animal behaviour literature describing privacy-related behaviours in different species. We found that animals use a variety of separation and information management mechanisms, whose function is to secure their own and their assets’ safety, as well as negotiate social interactions. In light of our findings, we question tacit assumptions and ordinary practices that involve human technology and that affect animal privacy. Finally, we draw implications for the design of interactive systems informed by animals’ privacy requirements and, more broadly, for the development of privacy-aware multispecies interaction design.